The efficacy of downhill running as a method to enhance running economy in trained distance runners - Shaw, A. J.; Ingham, S. A.; Folland, J. P. (European Journal of Sport Science, 2018)
Running downhill, in comparison to running on the flat, appears to involve an exaggerated stretch-shortening cycle (SSC) due to greater impact loads and higher vertical velocity on landing, whilst also incurring a lower metabolic cost. Therefore, downhill running could facilitate higher volumes of training at higher speeds whilst performing an exaggerated SSC, potentially inducing favourable adaptations in running mechanics and running economy (RE). This investigation assessed the efficacy of a supplementary 8-week programme of downhill running as a means of enhancing RE in well-trained distance runners. Nineteen athletes completed supplementary downhill (-5% gradient; n = 10) or flat (n = 9) run training twice a week for 8 weeks within their habitual training. Participants trained at a standardised intensity based on the velocity of lactate turnpoint (vLTP), with training volume increased incrementally between weeks. Changes in energy cost of running (EC) and vLTP were assessed on both flat and downhill gradients, in addition to maximal oxygen uptake ( O2max). No changes in EC were observed during flat running following downhill (1.22 ± 0.09 vs 1.20 ± 0.07 Kcal kg-1 km-1, P = .41) or flat run training (1.21 ± 0.13 vs 1.19 ± 0.12 Kcal kg-1 km-1). Moreover, no changes in EC during downhill running were observed in either condition (P > .23). vLTP increased following both downhill (16.5 ± 0.7 vs 16.9 ± 0.6 km h-1 , P = .05) and flat run training (16.9 ± 0.7 vs 17.2 ± 1.0 km h-1, P = .05), though no differences in responses were observed between groups (P = .53). Therefore, a short programme of supplementary downhill run training does not appear to enhance RE in already well-trained individuals.